A Systematic Review and Meta-synthesis of Indigenous Filipino Values in Educational Leadership - Dayson, Chris John P.; Ayo, John Paul D.; Equipado, Betty D.; Polon, Jeric H.; Buban, Robert G.; Digo, Gerry S. (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 4 (2024): October - December 2024DO - 10.14456/jcdr-hs.2024.24, 2024)
This systematic review and meta-synthesis investigate the Indigenous Filipino values in educational leadership in the Philippines. It explores Indigenous Filipino values in educational leadership, their implementation, the approaches, and the challenges encountered in implementing them. This review adhered to the PRISMA guidelines and utilized a research database consisting of ERIC, JSTOR, Scopus, ACI, Philippine E-Journals, and DLSU-indexed journals. The method employed the use of “keywords” and Boolean operators. The screening process entailed examining the abstracts, thoroughly reviewing the full texts of the published articles, and excluding those that did not meet the predetermined inclusion criteria. Additionally, non-English or Filipino papers were excluded. The systematic review ultimately included 26 studies from the 530 identified, focusing on educational leadership in the Philippines and engagement with Indigenous Filipino values.           The identified Filipino values were kapwa (shared identity), pakiramdam (shared inner perception), kagandahang-loob (shared humanity), kalayaan (freedom), and bahala na (determination). Their approach emphasizes collaboration, cultural responsiveness, empathy, student empowerment, critical thinking, resilience, creativity, and meeting community needs but faces challenges like colonial influences, limited cultural awareness, dominance of Western models, standardized testing, resource limitations, potential misunderstanding, and erosion of traditional values in implementing them.           The identified five Filipino values significantly impact education in the Philippines for effective leadership, promoting its potential while addressing the challenges. Future research should explore integrating Indigenous Filipino values alongside mainstream education. Keywords: Filipino Educational Leadership, Indigenous Filipino Values, Systematic Review